A novel radiation detector for removing scattered radiation in chest radiography: Monte Carlo simulation-based performance evaluation. (19th October 2016) - Roh, Y.H.; Yoon, Y.; Kim, K.; Kim, J.; Kim, J.; Morishita, J.
Abstract: Scattered radiation is the main reason for the degradation of image quality and the increased patient exposure dose in diagnostic radiology. In an effort to reduce scattered radiation, a novel structure of an indirect flat panel detector has been proposed. In this study, a performance evaluation of the novel system in terms of image contrast as well as an estimation of the number of photons incident on the detector and the grid exposure factor were conducted using Monte Carlo simulations. The image contrast of the proposed system was superior to that of the no-grid system but slightly inferior to that of the parallel-grid system. The number of photons incident on the detector and the grid exposure factor of the novel system were higher than those of the parallel-grid system but lower than those of the no-grid system. The proposed system exhibited the potential for reduced exposure dose without image quality degradation; additionally, can be further improved by a structural optimization considering the manufacturer's specifications of its lead contents.